The Identification of Alternatives and Changes in Scenarios for the Development of Regional Build Clusters - Chupryna, Yurij; Ryzhakov, Dmytro; Malykhina, Oksana; Pokolenko, Vadym (International Journal of Engineering and Technology, 2018)
The article deals with the creation of a general scheme for managing the structure of an integrated association under the influence of a complex of external and internal factors. This is the basis for identifying development scenarios or alternatives to the development of associations such as the construction cluster. Also, the article presents a method for detecting construction cluster development scenarios by comparing different building cluster management systems. The described models can be the basis for conducting expert appraisal and calculating the quality indicators of the management of associations on the basis of public-private partnership.Â Â
Keywords: building cluster; development scenario; management model; public-private partnership.